2002
DOI: 10.1183/09031936.02.00050502
|View full text |Cite
|
Sign up to set email alerts
|

Copenhagen City Heart Study: longitudinal analysis of ventilatory capacity in diabetic and nondiabetic adults

Abstract: The natural history of lung function in diabetes is unknown due to the lack of longitudinal observations. The decline of forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) was studied over 15 yrs in the 17,506 adult participants of The Copenhagen City Heart Study, which included 266 individuals with diabetes.Multiple linear regression and a mixed-effects model were used, taking into account correlation between repeated measurements and adjusting for relevant confounders. In both sexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 43 publications
7
84
1
Order By: Relevance
“…However, data are not completely in agreement on this topic, as two other longitudinal studies, based on follow-up periods of 5 and 15 years, respectively, have reported a similar decline in FVC and FEV1 in diabetic and in non-diabetic subjects [94,95]. However, these studies had some limitations.…”
Section: Decline In Lung Function Over Time and Its Clinical Implicationcontrasting
confidence: 45%
See 1 more Smart Citation
“…However, data are not completely in agreement on this topic, as two other longitudinal studies, based on follow-up periods of 5 and 15 years, respectively, have reported a similar decline in FVC and FEV1 in diabetic and in non-diabetic subjects [94,95]. However, these studies had some limitations.…”
Section: Decline In Lung Function Over Time and Its Clinical Implicationcontrasting
confidence: 45%
“…In the first one, 126 subjects who developed diabetes during the follow-up showed a decline in lung function that was at least twice that of nondiabetics [94]. The second study has limitations in the definition of diabetes, since the diagnosis was either self-reported by the patients or based on a single measurement of fasting blood glucose [95]. Subsequent studies have clearly demonstrated an accelerated decline in lung function in patients with diabetes.…”
Section: Decline In Lung Function Over Time and Its Clinical Implicationmentioning
confidence: 99%
“…The best FEV1 and FVC of three were used in the analyses. Lung function data are reported as a percentage of predicted value according to age, sex and height (FEV1 % pred) [13].…”
Section: Measurementsmentioning
confidence: 99%
“…Pulmonary involvement in diabetes is increasingly reported, [26][27][28][29][30][31][32][33] and may have important consequences if patients have co-morbid COPD. Routine spirometry to monitor lung function may therefore be useful in the care of patients with diabetes, particularly those who smoke.…”
Section: Disease Monitoringmentioning
confidence: 99%